Hematology Parameter Based on Tubex TF® Color Scale Result in Typhoid Fever Patients - Nugraheni, Enny; Syahrurachman, Agus; Dewi, Beti; Nainggolan, Leonard; Arodes, Evy Suryani; Mulyadi, Mulyadi (Open access Macedonian journal of medical sciences, 2022)
BACKGROUND: Infection with Salmonella enterica subspecies serovar Typhi and Paratyphi A, B, and C causes typhoid and paratyphoid fever. This is a major source of mortality and morbidity, especially in youngsters. Typhoid fever frequently causes non-specific symptoms. Symptoms that appear obstructively are comparable to those seen in other infectious illnesses and have similar clinical manifestations. Complications can be avoided with early detection and treatment. AIM: This study will look at the hematology parameter profile to determine whether there are any hematological differences between patients with high and low antibodies. METHODS: The research was conducted in Bengkulu, Indonesia, in June 2020 until July 2021. Subject collection was done according to inclusion and exclusion criteria. Subjects have given informed consent. The research included a total of 39 subject patients. Demographic data were collected using a questionnaire and 3 mL of blood was taken. Blood was examined for Tubex TF® and hematological examination. Statistical analysis used independent t-test and performed with SPSS. RESULTS: The research included a total of 39 subject patients. Most were male and most were aged 21–25 years. The most common symptom felt by the subject was gastrointestinal complaints. The analysis was carried out based on the color scale value of the Tubex TF® which was divided into two groups, 4 color scale groups and 6 color scale groups. Hematological parameters of hemoglobin, hematocrit, WBC, platelets, monocytes, lymphocytes, and neutrophils showed no significant difference. However, color scale group 6 showed lower value than 4 color scale group. CONCLUSION: Hematological indicators in typhoid fever were not substantially changed in Tubex TF®-positive typhoid fever patients. Clinicians can offer the same therapy in instances with typhoid fever, despite having differing positive Tubex TF® scores.